2020
DOI: 10.1109/access.2020.3022106
|View full text |Cite
|
Sign up to set email alerts
|

Control Scheme and Performance Analysis of Dual-Frequency Single-Phase Grid-Connected Inverter Interfaced With Weak and Distorted Grids

Abstract: Grid impedance variation and voltage harmonics may cause instability of the grid-connected inverter system and reduce the grid current quality under weak grid. Switching losses and electromagnetic interference of inverter can be reduced by using lower switching frequency. However, it is a challenging task to achieve stable operation of LCL-type grid-connected inverter using the active damping method at the low switching frequency. In this paper, an improved control strategy is proposed for the dual-frequency i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…According to (5), a frequency characteristic analysis of the Req1(ω) and Xeq1(ω) can be conducted, as shown in Fig. 4.…”
Section: A Modeling Of Lcl-type Grid-connected Invertermentioning
confidence: 99%
“…According to (5), a frequency characteristic analysis of the Req1(ω) and Xeq1(ω) can be conducted, as shown in Fig. 4.…”
Section: A Modeling Of Lcl-type Grid-connected Invertermentioning
confidence: 99%
“…Stiff Grid (ΔV, Δω) 0 Weak Grid or Islanded System (ΔV, Δω) > 0 (1) Short Circuit Ratio (2) X/R Ratio (3) Inertia Constant Distortion (4) The authors in [27] showed that the grid distortion increases the challenge of stabilizing the system even with small disturbance when the grid's inductive performance shifts the resonance frequency toward a lower frequency range. This is because the harmonic interactions induce the system instability and minimize the stability margins.…”
Section: Harmonics and Resonance Interaction Voltage Stabilitymentioning
confidence: 99%
“…Small grid impedance values result in a stiff grid with a high SCR. Large values of grid impedance seen at the POC result in a low SCR due to the increased voltage drop at the transmission lines [2][3][4]. This, in turn, deteriorates the voltage quality and the power transfer capability of the grid.…”
Section: Introductionmentioning
confidence: 99%
“…To solve the above-mentioned problems, a novel single-phase inverter was proposed in [25][26][27], which included two converters operating at different switching frequencies. One converter operated at low pulse ratio to inject current into the grid, while the other converter eliminated the grid current ripple with a high pulse ratio, using the feedforward compensation method.…”
Section: Introductionmentioning
confidence: 99%